MODEL LOG-LINIER G2 PADA OBSERVASI TRIVARIAT LENGKAP - I WAYAN SANTIYASA (Jurnal Matematika, 2007)
The log-linear models are most used to catagorical data analysis. The catagorical scale is thefunction transformation value form forth scale measured of observation : nominal, ordinal, ratioand interval. For the data analysis to trivariates observation of categorical scale is focus to createthe models with proof for interaction the factor in the models to 2-factor or 3-factor withgoodness-of-fit-test by G2 models.